In silico analysis of hub genes and regulatory networks implicates the putamen in non-motor Parkinson’s disease disorders - Stephen Tunmise Akanbi; Joshua Ayodele Yusuf; Thompson Oluwaferanmi Ayandele; Dayo Samson Oladipupo; Darasimi Racheal Olorunlowu; Blessing Dorcas Olawuyi; Joshua Oluwafisayo Adepoju; Dolapo Emmanuel Opasina; Elizabeth Kehinde Opoola; Uchenna Victor Ugwuanyi; Olufunto Omodele Adeleye (Egyptian Journal of Medical Human Genetics)
Abstract Background Parkinson’s disease (PD) is a neurodegenerative condition marked by the gradual degeneration of dopaminergic neurons in the substantia nigra, leading to depletion of the dopaminergic neurons in the substantia nigra as well as degeneration as and decreased activity in the putamen. This study aims to identify the role of putamen in non-motor PD symptoms as well as potential therapeutic target in the putamen of PD. Methods Transcriptome profiles of PD (dataset number: GSE205450, obtained from postmortem putamen and caudate samples from forty controls and thirty-five PD patients) were retrieved from the Gene Expression Omnibus (GEO) database. Specifically, we focused on putamen data for controls and PD patients. Differential gene expression analysis was carried out using with Limma, filtering for genes with |logFC|> 1 (fold change) and p < 0.05 (p-value). Protein–Protein Interaction networks were constructed using stringDB (combined score > 0.7) and analyzed in Cytoscape to identify hub genes based on various topological measures (EPC, MCC, MNC, Degree, and EcCentricity). Enrichment analysis of target genes was conducted using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). Also, we constructed transcription factor (TF)-hub gene expression networks, miRNA-hub gene expression networks, and disease hub gene association networks using the JASPAR database, Tarbase database, and DisGeNET via NetworkAnalyst platform, respectively. Results Seven genes, namely SST, NPY, IL6, PVALB, ALB, NTS, and TH were identified as hub genes in PD putamen. Notable miRNAs included hsa-mir-34a-5p, hsa-mir-15a-5p, hsa-mir-424-5p, and hsa-mir-19b-3p, while key transcription factors include GATA2, CREB1, FOXC1, FOXL1, TID1, NFKB1, YY1, SPIB, GATA3, and STAT3. Conclusions Our findings revealed close associations between the hub genes of PD putamen and non-motor symptoms of PD such as major depressive disorder, mood disorders and schizophrenia. These findings may provide a new direction for developing therapy for non-motor symptoms of PD and wet lab research is encouraged.